Alterations in the general condition, biochemical parameters and locomotor activity in Cnesterodon decemmaculatus exposed to commercial formulations of chlorpyrifos, glyphosate and their mixtures - Bonifacio, Alejo Fabian (2016)
The Pampean region, an extensive area of South America is continuously impacted by agricultural activities and the pesticides related to them like chlorpyrifos and glyphosate. Both pesticides have been registered in freshwater bodies of the region. One of the most abundant and widely distributed fish species in Pampean streams is Cnesterodon decemmaculatus, which have to cope with this altered scenario. In the present study the toxicity of Clorfox®and Roundup Max®, the commercial formulations of chlorpyrifos and glyphosate, respectively, and their mixture where evaluated using a set of biomarkers at different biological organization levels in fish exposed to relevant environmentally pesticides con-centrations. Somatic indexes such as the condition factor (K), and the hepato-somatic index (HSI), the locomotor activity through the distance traveled and the average speed, the enzymatic activities of acetyl-cholinesterase (AChE) in brain and muscle, catalase (CAT) in muscle and liver, glutathione-S-transferase(GST) in brain, liver, muscle and gills, aspartate amino-transferase (AST), alanine amino-transferase (ALT),AST/ALT ratio and alkaline phosphatase (ALP) in liver were measured on C. decemmaculatus. Adult females were exposed during 6 weeks to the following concentrations: 0.0084 ul/l and 0.00084 ul/l of Clorfox(CF), 0.2 and 2 mg/l of Roundup Max (RM) and all the combinations of these concentrations. The CF exposure caused a decrease in the condition factor and in the locomotor activity parameters and induced an increase brain AChE, liver CAT activity and AST/ALT ratio. On the other hand, the exposure to RM produced a decrease in liver GST, AST/ALT ratio and ALP activity. Finally, some pesticide combinations decrease general condition and liver GST activities, and increase brain GST and liver ALP activities. Different responses in biomarkers were observed in mixtures treatments, reflecting the complex interactions between these toxics and suggesting a suppressive action of RM on CF effects. Since the concentrations we tested are environmentally relevant and the overall fish health conditionwas affected, the presence of these pesticides in freshwater systems could impose a risk for populations by causing deleterious effects on C. decemmaculatus in Pampean region.